Preparation method and application of Prussian blue analogue composite material

By combining the Prussian blue analog composite material derived from the bimetallic zeolite imidazole frame with advanced persulfate oxidation technology, the CoFex-ZIF/PBA/PMS/Vis advanced oxidation technology system was constructed, which solved the problems of high cost of oxidant use and difficulty in operation in the existing technology, and achieved the effect of efficient removal of persistent organic pollutants in water bodies.

CN119657227APending Publication Date: 2025-03-21JIANGSU JIANGKE NEW COMPOSITE MATERIAL CO LTD +2
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411504797.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-27
Publication Date
2025-03-21

AI Technical Summary

Technical Problem

The prior art has problems such as high cost of using oxidants, difficult operation, difficult reaction process, and low removal efficiency when treating persistent organic pollutants in water bodies.

Method used

The Prussian blue analog composite material derived from bimetallic (cobalt and iron) zeolite imidazole frame is combined with advanced persulfate oxidation technology to construct a CoFex-ZIF/PBA/PMS/Vis advanced oxidation technology system for the removal of organic pollutants.

Benefits of technology

It has achieved efficient removal of persistent organic pollutants in water, with high PMS utilization efficiency, good decontamination activity, wide pH application range, strong anti-interference ability, high stability and simple operation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119657227A_ABST
    Figure CN119657227A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a prussian blue analogue composite material derived from a bimetallic (cobalt and iron) zeolite imidazole framework. A bimetallic (cobalt and iron) zeolite imidazole framework (CoFex-ZIF) is used as a self-sacrifice template, cobalt and iron Prussian blue analogues (PBA) grow in situ on the CoFex-ZIF at room temperature according to an ion exchange strategy, then a CoFex-ZIF / PBA composite material is successfully prepared and combined with an advanced oxidation technology, and a CoFex-ZIF / PBA / PMS / Vis advanced oxidation technology system is constructed and used for removing organic pollutants. Wherein the CoFe < 2.5 >-ZIF / PBA / PMS / Vis system has ultrahigh PMS utilization efficiency (71%) and good decontamination activity (the rate constant is 1.081 min <-1 >), and the CoFe < 2.5 >-ZIF / PBA / PMS / Vis system exceeds most heterogeneous Fenton advanced oxidation catalysts.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0002] The present invention relates to the field of advanced oxidation treatment of wastewater and the technical field of nanocomposite materials, and in particular to a method for preparing a composite material of a Prussian blue analogue derived from a bimetallic (cobalt and iron) zeolite imidazole framework and its application in synergistic persulfate advanced oxidation technology in removing organic pollutants from water bodies. Background Art

[0003] Pesticides have the function of preventing and controlling crop diseases and ensuring the normal growth of crops. They are widely used in agricultural and food industry production to meet the growing food demand brought about by the world's population explosion. However, the large-scale use of various pesticides has brought about various environmental problems. Taking the widely used imidacloprid (IMD) as an example, in the IMD short-term exposure experiment, IMD may cause potential reproductive toxicity and genotoxicity in humans and other vertebrates. Therefore, it is crucial to seek an effective and sustainable treatment technology to eliminate the ecological and environmental risks of IMD in the water environment. The Fenton-like process based on peroxymonosulfate (PMS) has been proven to be a clean and effective technology for the treatment of persistent organic pollutants by catalytically activating PMS to produce reactive oxygen species (ROS). Among them, the asymmetric structure (HO-OSO3 - ) and PMS with longer OO bonds can be catalyzed by external field energy (heat, light, ultrasound, microwaves, etc.), transition metal ions / compounds (Co 2+ , Fe 2+ , Co3O4, etc.) and metal-free materials (carbon-based, boron-based, and sulfur-based). Activating PMS by coupling the inherent active sites of the material with the continuous injection of photogenerated electrons can effectively improve the activation efficiency of PMS. In addition, the adsorption of PMS and intermediate substances, as well as the related electron transfer process, are considered to be the key steps in PMS activation and ROS generation. Therefore, it is crucial to design materials that can accelerate electron transfer, thereby improving the activation efficiency of PMS. This study aims to develop a photocatalyst that can effectively activate PMS and generate a large amount of ROS for ultrafast degradation of IMD in water.

[0004] Metal-organic frameworks (MOFs) are a class of materials with adjustable pore sizes formed by the self-assembly of organic ligands and metal centers. Compared with traditional inorganic porous materials, MOFs have larger specific surface area, higher porosity, and more diverse structures and functions, which make them widely used in gas adsorption and separation, sensors, drug sustained release, and catalytic reactions. Materials related to MOFs are mainly divided into two categories: original MOF materials and MOFs-derived materials. As a member of this group, ZIF-67 has sufficient divalent cobalt and high specific surface area, and is an ideal precursor under reasonable modification (e.g., metal doping substitution). Prussian blue analogs (PBAs) have three-dimensional (3D) open frameworks, adjustable compositions, and controllable structures, and the transition metal center is surrounded by six cyanide groups (C≡N). In recent years, PBAs have attracted widespread attention for the activation of PMS under visible light, which means that PBAs are expected to be used as catalysts for treating persistent and refractory organic pollutants in water. Benefiting from the advantages of both MOFs, the combination of zeolitic imidazolate framework (ZIF) and PBA can be an effective method to enhance PMS activation and promote the oxidative degradation of pollutants in water, which is a promising work.

[0005] In addition, the traditional homogeneous Fenton reaction mainly includes the following disadvantages: large iron sludge production, narrow pH working range, large hydrogen peroxide consumption, large amount of acid and alkali used, high difficulty in operation, etc. The Prussian blue analog CoFe2.5-ZIF / PBA catalyst prepared by the present invention has a wide pH application range, strong anti-interference ability, high stability and low Co ion leaching in the process of removing persistent organic pollutants by using persulfate advanced oxidation technology, and is simple to operate and environmentally friendly, and has potential practical application value in the field of advanced oxidation treatment of wastewater. Summary of the invention

[0006] In order to solve the problems of the prior art, the technical solution adopted by the present invention is:

[0007] Using bimetallic (cobalt and iron) zeolite imidazole framework (CoFex-ZIF) as a self-sacrificial template, cobalt and iron Prussian blue analogs (PBA) were in situ grown on CoFex-ZIF at room temperature by ion exchange strategy. Subsequently, CoFex-ZIF / PBA composite materials were successfully prepared and combined with advanced oxidation technology to construct a CoFex-ZIF / PBA / PMS / Vis advanced oxidation technology system for the removal of organic pollutants, which specifically includes the following steps:

[0008] (1) Catalyst preparation:

[0009] Step 1, dissolve 2g Co(NO3)2·6H2O and 6.6g 2-dimethyl zeolite imidazole in 20-30mL methanol respectively, and then stir at 30°C at a speed of 1000r / min for 2h to obtain suspension A for use.

[0010] Step 2: Dissolve 1-3 g Fe(NO3)3·9H2O in 50 mL methanol solution and heat at 30°C at 1000 °C.

[0011] The mixture was stirred at a speed of r / min for 2 h and further poured into the suspension A prepared in step 1. Finally, the solid was collected by centrifugation after washing three times with methanol and then dried at 80°C overnight. The prepared sample was named CoFex-ZIF.

[0012] Step 3, first, 0.05-0.1 g of the prepared CoFex-ZIF was dispersed in 50-100 mL of ethanol, and then after ultrasonic treatment for 1-3 h, 50-100 mL of potassium ferricyanide aqueous solution (1-1.5 g / L) was added for aging for 3-7 h, and the solid was collected by centrifugation. Then it was dried at 80 ° C overnight. The prepared sample was named CoFex-ZIF / PBA.

[0013] (2) Application of CoFex-ZIF / PBA / PMS / Vis advanced oxidation system:

[0014] Step 4, take 5-20 mg CoFex-ZIF / PBA catalyst and disperse it in 100 mL of organic pollutants (imidacloprid (IMD), rhodamine B (RhB), 2-mercaptobenzothiazole (MBT), tetracycline (TC), bisphenol A (BPA), sulfamethoxazole (SMX), etc.) aqueous solution (concentration range: 1-30 mg / L), add 10-40 mg PMS and detect the residual concentration of IMD every 2 minutes under light.

[0015] Step 5, take 5-20 mg CoFex-ZIF / PBA catalyst and disperse it in 100 mL of imidacloprid solution (concentration range: 1-30 mg / L), adjust the initial pH of the solution (3-9), add 100-600 mg PMS and 0-1 mmol interfering agent (sodium chloride, sodium sulfate, sodium nitrate, sodium bicarbonate), and detect the residual concentration of IMD every 2 minutes under light.

[0016] Beneficial effects:

[0017] Compared with the prior art, a preparation method of a Prussian blue analog composite material and its application have the following advantages:

[0018] (1) The present invention uses a bimetallic (cobalt and iron) zeolite imidazole framework (CoFex-ZIF) as a self-sacrificial template, and in situ grows cobalt and iron Prussian blue analogs (PBA) on CoFex-ZIF at room temperature using an ion exchange strategy, and then successfully prepares a CoFex-ZIF / PBA composite material and combines it with advanced oxidation technology for the removal of organic pollutants. The oxidant used in the traditional Fenton technology is hydrogen peroxide, which not only has high processing costs, is difficult to operate, and is difficult to control the reaction process, but also has unsatisfactory treatment effects; while the CoFex-ZIF / PBA / PMS / Vis advanced oxidation technology system constructed by the present invention uses PMS as an oxidant, which has more stable properties, milder reaction conditions, controllable reaction process, faster reaction rate, and relatively low cost.

[0019] (2) The CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation technology system has an ultra-high PMS utilization efficiency (71%)

[0020] and good decontamination activity, surpassing most state-of-the-art heterogeneous Fenton-type catalysts. In particular, 98.9% IMD was achieved in only 4 min at 0.05 g / L CoFe2.5-ZIF / PBA and 0.3 g / L PMS.

[0021] (10mg / L) removal rate, rate constant is 1.081min -1 This shows that the technology provided by the present invention can greatly enhance the catalytic removal efficiency of pollutants.

[0022] (3) The CoFex-ZIF / PBA / PMS / Vis advanced oxidation technology system constructed in the present invention has a high removal rate for IMD in the pH range of 5 to 9, which solves the shortcomings of the current Fenton technology that the acidity must be adjusted and the pH range is narrow.

[0023] (4) The present invention constructs a CoFex-ZIF / PBA / PMS / Vis advanced oxidation technology system, which has a simple and easy preparation process, is applicable to a variety of pollutants, has the ability to be reused, and has a low metal ion leaching concentration. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 .XRD patterns of different catalysts prepared in Examples 1-3.

[0025] Figure 2 .Fourier transform infrared (FT-IR) spectral analysis of CoFe2.5-ZIF and CoFe2.5-ZIF / PBA catalysts prepared in Example 1.

[0026] Figure 3.Specific surface area (BET) and pore size distribution of CoFe2.5-ZIF and CoFe2.5-ZIF / PBA catalysts prepared in Example 1.

[0027] Figure 4 (a) and (b) are scanning electron microscopy and transmission electron microscopy images of the sample prepared in Example 1, respectively.

[0028] Figure 5 (a) Performance test curves of different advanced oxidation systems constructed for Examples 1 to 3. (b) First order reaction kinetic rates of different systems.

[0029] Figure 6 (a) Performance test of CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system at different pH values. (b) Performance test of CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system under different interferences.

[0030] Figure 7 (a) Degradation test of different pollutants in water by CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system. (b) Degradation test of IMD by CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system in different water sources.

[0031] Figure 8 This is the visible light synergistic PMS catalytic degradation activity diagram of pollutants after 5 cycle experiments of the sample prepared in Example 1 and the Co ion leaching experiment during the reaction process.

[0032] Fig. 9 .PMS decomposition efficiency of CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system.

[0033] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art in the art described herein. Although the present invention only describes preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials related to the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.

[0034] Example 1 Preparation of CoFe2.5-ZIF / PBA Catalyst and Application of CoFe2.5-ZIF / PBA / PMS / Vis Advanced Oxidation System

[0035] (1) Preparation of CoFe2.5-ZIF / PBA catalyst:

[0036] Step 1, dissolve 2g Co(NO3)2·6H2O and 6g 2-dimethyl zeolite imidazole in 25mL methanol respectively, and then stir at 30°C and 1000r / min for 2h to obtain suspension A for use.

[0037] Step 2, 1g Fe(NO3)3·9H2O was dissolved in 50mL methanol solution, stirred at 1000r / min for 2h at 30℃, and further poured into the suspension A prepared in step 1. Finally, the solid was collected by centrifugation after washing three times with methanol and then dried at 80℃ overnight. The prepared sample was named CoFe2.5-ZIF.

[0038] Step 3: First, 0.05 g of the prepared CoFe-ZIF was dispersed in 50 mL of ethanol, and then after ultrasonic treatment for 1 h, 50 mL of potassium ferrocyanide aqueous solution (1 g / L) was added and aged for 3 h, and the solid was collected by centrifugation.

[0039] The prepared sample was named CoFe2.5-ZIF / PBA.

[0040] (2) Application of CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system:

[0041] Step 4: Take 5 mg of CoFe2.5-ZIF / PBA catalyst and disperse it in 100 mL of IMD solution (concentration:

[0042] 10 mg / L), 30 mg PMS was added and the residual concentration of IMD was detected every 2 min under light.

[0043] Step 5, take 5-20mg CoFe2.5-ZIF / PBA catalyst and disperse it in 100mL imidacloprid solution (concentration range: 1-30mg / L), the initial pH of the solution is 7, add 100-600mg PMS and 0mmol interfering agent (sodium chlorosulfate, sodium nitrate, sodium bicarbonate) under light, and detect the residual concentration of IMD every 2min. Example 2 Preparation of CoFe2-ZIF / PBA catalyst and application of CoFe2-ZIF / PBA / PMS / Vis advanced oxidation system The steps of this embodiment are similar to those of embodiment 1, except that 0.8g Fe(NO3)3·9H2O is added in step 2, and the catalyst prepared in this embodiment 2 is named CoFe2-ZIF / PBA, and a CoFe2-ZIF / PBA / PMS / Vis advanced oxidation system is constructed.

[0044] Example 3 Preparation of CoFe3-ZIF / PBA catalyst and application of CoFe3-ZIF / PBA / PMS / Vis advanced oxidation system The steps of this example are similar to those of Example 1, except that 1.2 g Fe(NO3)3·9H2O is added in step 2, and the catalyst prepared in this example 3 is named CoFe3-ZIF / PBA, and a CoFe3-ZIF / PBA / PMS / Vis advanced oxidation system is constructed.

[0045] Morphology and characterization tests

[0046] 1. Material Characterization

[0047] 1. XRD analysis, Fourier transform infrared (FT-IR) spectroscopy analysis and specific surface area analysis.

[0048] Figure 1 XRD patterns of different catalysts prepared in Examples 1-3. Figure 1 a is CoFex-ZIF prepared by adding different masses of Fe(NO3)3·9H2O. Figure 1 b is the final catalyst CoFex-ZIF / PBA prepared by the present invention.

[0049] XRD studies revealed that the diffraction peaks of CoFex-ZIF matched well with the simulated card of ZIF-67, but the introduction of increasing amounts of iron nitrate led to a decrease in the crystallinity of the crystals. In addition, CoFex-ZIF / PBA described characteristic diffraction peaks at 17.58°, 24.96°, and 35.59°, which correspond to the (200), (220), and (400) crystal planes of K2CoFe(CN)6 (JCPDS No.75-0038). However, only the diffraction peaks of K2CoFe(CN)6 were detected in CoFex-ZIF / PBA, and the diffraction peaks corresponding to the CoFex-ZIF crystal structure disappeared. This result may be due to the following reasons: (1) The relative content of CoFex-ZIF in the composite material decreased as a sacrificial template after subsequent in situ ion exchange. (2) PBA nanoparticles covered the surface of CoFex-ZIF.

[0050] Figure 2 Fourier transform infrared (FT-IR) spectroscopy analysis of the CoFe2.5-ZIF and CoFe2.5-ZIF / PBA catalysts prepared in Example 1. Figure 2 The Fourier transform infrared (FT-IR) spectra of all samples showed a 600-1600 cm -1 Vibration. 1580cm -1The absorption peak at 1420 cm is attributed to the stretching mode of the C=N bond in imidazole. The characteristic peak of the stretching vibration of the entire imidazole ring is concentrated at 1420 cm -1 and 1305cm -1 In addition, the 426 cm -1 The absorption peak at 1000 cm in CoFe2.5-ZIF is attributed to the Co-N bond in ZIF. -1 and 1100cm -1 Two new peaks appeared between them. This may be due to the introduction of Fe 3+ These results indicate that Fe 3 + It was successfully introduced without destroying the main structure of the imidazole ring. -1 and 592cm -1 Two absorption peaks appeared at , corresponding to the stretching of C≡N bond and M-CN-M' (M = metal). Both peaks are evidence of the successful synthesis of PBA nanoparticles. Obviously, the intensity of several main peaks of imidazole ring in CoFe2.5-ZIF / PBA was significantly reduced, which is due to the introduction of Fe(CN)6 3– result.

[0051] Figure 3 The BET surface area and pore size distribution of the CoFe2.5-ZIF and CoFe2.5-ZIF / PBA catalysts prepared in Example 1 are shown in Figure 1. The BET surface area and pore volume of CoFe2.5-ZIF and CoFe2.5-ZIF / PBA were obtained by N2 absorption-desorption analysis. Figure 3 As shown in Figure 5, the BET surface area and pore size of CoFe2.5-ZIF / PBA are much smaller than those of CoFe2.5-ZIF, which may be due to the tightly grown PBA nanoparticles covering the surface of CoFe2.5-ZIF and occupying the pore size of CoFe2.5-ZIF.

[0052] 2. Morphology Analysis

[0053] Further analysis of the morphological characteristics of the catalyst materials prepared by the research. Figure 4 (a) and (b) are scanning electron microscopy and transmission electron microscopy images of the sample prepared in Example 1, respectively, indicating that the synthesized catalyst has a three-dimensional hollow morphology. The three-dimensional hollow structure of CoFe2.5-ZIF / PBA can promote electron transport between active sites and PMS, greatly improving the removal efficiency of organic pollutants.

[0054] 2. Performance Test

[0055] 1. Performance test of CoFex-ZIF / PBA / PMS / Vis advanced oxidation system.

[0056] A 100mL double-layer jacketed beaker was used as the reactor for the pollutant degradation performance test, wherein circulating cooling water was introduced into the jacket of the double-layer jacketed beaker to eliminate the heat generated by the light source during the catalytic reaction, thereby ensuring that the organic pollutant performance test was carried out at room temperature and pressure. Under visible light (λ≥420nm), the performance of the CoFex-ZIF / PBA / PMS / Vis advanced oxidation system was tested by degradation of organic pollutants, and an air pump was used to continuously blow air into the reaction system. The catalytic experiment was carried out by adding 5mg of catalyst to 100mL of organic pollutant solution (10-30mg L -1 ). First, balance in the dark for 30 minutes to reach adsorption-desorption equilibrium. After adsorption equilibrium, add 30 mg of PMS, turn on the light source, take out 1 mL of degradation solution every 2 minutes, then immediately stop the reaction with 1 mL of methanol and filter with 0.22 μm nylon membrane to test the concentration of remaining organic pollutants.

[0057] Figure 5 (a) Performance test curves of different advanced oxidation systems constructed in Examples 1-3. It can be seen that the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system exhibits excellent PMS activation ability, and the IMD removal efficiency is significantly improved compared with the CoFe2-ZIF / PBA / PMS / Vis advanced oxidation system and the CoFe3-ZIF / PBA / PMS / Vis advanced oxidation system. Figure 5 Based on the data (a), the reaction rate (k) of catalyst degradation of IMD was calculated according to the pseudo-first-order kinetic model, as follows: Figure 5 (b) The reaction rate of the catalyst for IMD degradation in the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system constructed in Example 1 is 1.081 min -1 , while the advanced oxidation systems constructed in Example 2 and Implementation 3 were 0.607min -1 and 0.063min -1 . Combined Figure 5 (a) It can be found that the catalytic activity of the catalyst in Example 1 is the highest, and the reaction rate can reach 1.081 min -1 .

[0058] 2. Performance test of CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system under different conditions.

[0059] (1) Figure 6(a) Performance test of CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system at different pH. Figure 5 It can be seen that the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system can achieve rapid removal of IMD in a wide pH range (5-9). Compared with the traditional Fenton technology, the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system constructed in the present invention has milder operating conditions.

[0060] (2) Figure 6 (b) Performance test of CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system under different interferences. Figure 5 It can be seen that the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system can still achieve rapid removal of IMD in the presence of different ion interferences. The CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system constructed in the present invention has strong anti-interference ability.

[0061] (3) Figure 7 (a) is the degradation test of different pollutants in water by CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system. Figure 7 (a) It can be seen that the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system has the ability to rapidly degrade a variety of pollutants, indicating that the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system constructed in the present invention has universal applicability.

[0062] (4) Figure 7 (b) is the degradation test of IMD in different water sources by CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system. Figure 7 (b) It can be seen that the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system has a strong IMD degradation ability in Yangtze River water, tap water and pure water, indicating that the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system constructed in the present invention has great practical application potential.

[0063] (5) Figure 8 The activity diagram of the visible light synergistic PMS catalytic degradation of pollutants and the Co ion leaching experiment during the reaction process of the sample prepared in Example 1 after 5 cycles of experiments are shown in FIG. Figure 8As shown, it was found that CoFe2.5-ZIF / PBA exhibited excellent durability and repeatability after 5 cycle tests, and the leaching of Co ions was close to 0.3 mg / L, indicating that the CoFe2.5-ZIF / PBA catalyst has high stability and low Co ion leaching and is environmentally friendly.

[0064] In summary, the present invention discloses a method for preparing a Prussian blue analog composite material and its application in an advanced oxidation system. Characterization results show that the synthesized catalyst is a three-dimensional hollow structure. The three-dimensional hollow structure of CoFe2.5-ZIF / PBA can promote electron transfer between active sites and PMS, greatly improving the removal efficiency of organic pollutants. In the CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system constructed in Example 1, the reaction rate of the catalyst for degrading IMD is 1.081 min -1 The CoFe2.5-ZIF / PBA / PMS / Vis advanced oxidation system can achieve rapid degradation of IMD in a wide pH range, in the presence of interferents, and in different water sources. Cyclic experiments and ion leaching tests showed that the CoFe2.5-ZIF / PBA catalyst has high stability and low Co ion leaching, is environmentally friendly, and has potential practical application value in the field of advanced oxidation wastewater treatment.

[0065] The above is only a preferred specific implementation manner of the present invention, and the protection scope of the present invention is not limited thereto. Any simple change or equivalent replacement of the technical solution that can be obviously obtained by any technician familiar with the technical field within the technical scope disclosed in the present invention falls within the protection scope of the present invention.

Claims

1. A preparation method and application of a Prussian blue analog composite material, characterized in that: CoFex-ZIF / PBA was prepared by in situ growth of cobalt and iron Prussian blue analogs (PBA) on CoFex-ZIF using a cobalt and iron bimetallic zeolite imidazole framework as a self-sacrificial template by an ion exchange strategy at room temperature, specifically comprising the following steps: Step 1, dissolve 2-3g Co(NO3)2·6H2O and 5-7g 2-dimethyl zeolite imidazole in 20-30mL methanol respectively, and then stir at 30°C and 1000r / min for 2-4h to obtain suspension A for standby use. Step 2, 1-3 g Fe(NO3)3·9H2O was dissolved in 50-100 mL methanol solution, stirred at 1000 r / min for 2-4 h at 30°C, and further poured into the suspension A prepared in step 1. Finally, the solid was collected by centrifugation after washing three times with methanol and then dried at 80°C overnight. The prepared sample was named CoFex-ZIF. Step 3, first, 0.05-0.1 g of the prepared CoFex-ZIF was dispersed in 50-100 mL of ethanol, and then after ultrasonic treatment for 1-3 h, 50-100 mL of potassium ferricyanide aqueous solution (1-1.5 g / L) was added for aging for 3-7 h, and the solid was collected by centrifugation. Then it was dried at 80 ° C overnight. The prepared sample was named CoFex-ZIF / PBA.

2. The preparation method and application of a Prussian blue analog composite material according to claim 1, characterized in that: The stirring conditions in step 1 are: stirring at 30° C. and at a speed of 1000 r / min for 2-4 h.

3. The preparation method and application of a Prussian blue analog composite material according to claim 1, characterized in that: The stirring conditions in step 2 are: stirring at 30°C and at a speed of 1000 r / min for 2-4 hours.

4. The preparation method and application of a Prussian blue analog composite material according to claim 1, characterized in that: In step 3, CoFex-ZIF is used as a sacrificial template to prepare a Prussian blue analog composite material. The aging time is 3-7 hours, and the concentration of the potassium ferrocyanide aqueous solution is 1-2 g / L.

5. Use of a Prussian blue analog composite material prepared by any one of the methods of claims 1 to 4 in treating organic pollutants in water using advanced oxidation technology.